EVIDENCE FOR MS SERVICES: FINDINGS OF THE MS TRUST'S GEMSS PROGRAMME. Issue 12 (15th November 2016) - Bowen, Amy; Mynors, Geraldine; Suppiah, Jane
Abstract : In 2012 the MS Trust identified a lack of robust evidence for MS specialist nursing. The Trust's 'Generating Evidence in MS Services' (GEMSS) programme supported fifteen MS specialist teams to evaluate their services over 2014–15. Teams were selected to represent UK services and had a combined caseload of over 15, 000 people with MS. They collected information about caseload, activity and key process indicators, and distributed a specially designed patient survey. Facilitation and analysis was undertaken by the MS Trust. GEMSS demonstrated that MS nurses are the most consulted professionals about MS, contribute to all domains of the NHS Outcomes Framework, increase the capacity of other clinicians, particularly neurologists, and save NHS costs. However findings also highlighted service iniquities. Caseload analysis highlighted that people with RRMS represent only 51% of combined caseloads but utilise a disproportionate share of neurologist and MS nurse time. It also showed wide variation in DMD prescribing rates and use of different therapies between teams. GEMSS has increased the confidence and knowledge of evaluation in participating teams and created a unique compendium of information about services. Finally, it has laid the foundations for MS Forward View, a new programme launched by the MS Trust in January 2016.